Are Turkish pharmaceutical pricing strategies an access barrier to oncology medicines for Türkiye? - Vural, Elif Hilal; Kaskati, Tolga; Vural, İsmail Mert; Özalp, Mustafa Asım; Gümüşel, Bülent (Frontiers in Pharmacology, 2024)
Cancer diagnosis is increasing day by day all over the world. Deaths due to cancer are among the common causes of death. Access to cancer drugs is a priority of health policies. The aim of this study is to evaluate access to cancer drugs through drug box sales data by modeling population growth, cancer incidence and Fixed Euro Exchange (FEE) rate parameters used in drug pricing in Turkiye.Access to cancer drugs was evaluated by drug box sales figures obtained from IQVIA. Box sales data classified according to diagnosis codes (ICD-10), reference or generic status. Consumption of cancer drugs was examined over time with panel regression analysis, taking into account variables of population growth, cancer incidence and FEE rate in drug pricing in Turkiye.The incidence of cancer in Turkiye was 215.1 in 2010 and 223.1 (per hundred thousand) in 2017. While there was a 127.02% increase in the real euro exchange rate, there was 89.6% increase in the FEE rate. With the regression approach, there is a negative relationship between the Reel and Fixed Exchange Rate Difference (RFED) and reference and generic drug consumption data. Medicine access is affected depending on diagnosis codes at different levels.Conclusions: According to our results pricing strategy may be access barriers for oncology medicines in Turkiye. It should be reviewing the pricing policy beneficial for oncology medicine access for Turkiye.